Construction of the Cognitive Dimension of the Scientific Literacy in the Students through the Costa Rican Biological Sciences Olympics - Camacho Vargas, Shirley (2012)
This research recognizes the cognitive contributions to the students participating in the Third Costa Rican Biological Sciences Olympics that will define the advancement and strengthening in the construction of its conceptual dimension in the scientific literacy.  This paper is based, mainly, on qualitative approach techniques (ethnographic design:  case study); however, some data are interpreted through quantitative methodologies (descriptive design with an explanatory and exploratory touch) for the analysis of a sample of 54 high school students, finalists in the category A of the Olympics, through the use of tools such as a documentary study and a survey, in July 2009.  The information generated was analyzed using elements of inferential and descriptive statistics, figures and histograms.  It was proved that there is a better cognitive management in the topics assessed, an increase in the students’ academic performance as the tests are applied, a commitment for the academic update supported by the development of several tasks for previous preparation, curriculum contributions unprecedented based on our sample, a consent to optimize student’s knowledge about Biology, which will allow the application of scientific notions to diversify and renew the knowledge, according to what is established in the principles of scientific literacy.